4 - Concepts et approches pour une définition de l’espace sahélien: by Boureima Alpha Gado - Boureima Alpha Gado (Africa Development, 1993)
How does one define precisely what the Sahel is? Where does it start and where does it end? That is the difficulty facing any researcher trying to grasp the physical and human contours of the Sahelian space. After reviewing all existing definitions and shortcomings of the Sahelian space, the author suggests another definition. What makes the Sahelian space original is that the Sahel is at the junction between two worlds. It is a moving space with fragile equilibrium. What makes the equilibrium fragile is the complexicity and interaction of the limiting factors. The respective impacts of nature and history and may have rendered the Sahelian space an underdevelopped region where there is the abominable cycle of drought and famine.